Fabrication of immunomodulatory interface layers for medical implants through additive manufacturing. (2022) - Yew, Dionis Si Ying; See, Peter; Beh, Cyrus W.
Abstract: The development of various types of medical implants in the last few decades have helped prolong and improve patient's quality of life. However, with rare exception, implants have generally been made out of traditional engineering materials such as metals, plastics, and elastomers. Biocompatibility of these materials has been largely defined by their inert nature, which, when introduced into the host, will result in the foreign body response (FBR). Although generally considered acceptable, FBR may impair the performance or reduce the lifespan of the implants due to the formation of a fibrous capsules. In certain applications, this fibrous capsule formation may cause a sufficiently reduction in performance to warrant revision surgery to either replace the implant or remove the fibrous tissues, thereby causing additional stress and discomfort to the patient. Thus, in this project we aim to utilize Additive manufacturing to create an anti-fouling hydrogel coating on a titanium alloy to achieve immunomodulatory effects.